Focus of Attention During ACL Injury Prevention Exercises Affects Improvements in Jump-Landing Kinematics in Soccer Players: A Randomized Controlled Trial. Issue 2 (23rd February 2023) - Dalvandpour, Nazanin; Zareei, Mostafa; Abbasi, Hamed; Abdoli, Behrouz; Mohammadian, Mohammad A.; Rommers, Nikki; Rössler, Roland
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Dalvandpour, N, Zareei, M, Abbasi, H, Abdoli, B, Mohammadian, MA, Rommers, N, and Rössler, R. Focus of attention during ACL injury prevention exercises affects improvements in jump-landing kinematics in soccer players: a randomized controlled trial. J Strength Cond Res 37(2): 337–342, 2023—Anterior cruciate ligament tears are severe and complex knee injuries that commonly occur in soccer. Prevent injuries enhance performance (PEP) is an exercise-based prevention program to effectively reduce anterior cruciate ligament injuries. It is, however, unclear how the delivery of the program contributes to its effectiveness. Therefore, we aimed to investigate the effect of the focus of attention that was emphasized during the delivery of the PEP program on jump-landing kinematics in male, elite-level, U21 soccer players. Forty-two players participated in this randomized controlled trial and were allocated to (a) the internal focus of attention (IF) group, receiving instructions focusing on the execution of the exercise (b), the external focus of attention (EF) group, receiving instructions focusing on the outcome of the exercise, or (c) the control group. Before and after the 8-week intervention, players performed a jump-landing task during which we measured hip and knee angles at the initial contact, peak knee flexion, and peak vertical ground reaction force using a 3-dimensional motion analyzer. A repeated-measures analysis of variance was used to compare groups over time. Significant time-by-group interaction effects with large effect sizes were found for hip flexion at all moments ( p < 0.032; η 2 > 0.15) and for the knee flexion angle at initial contact and maximum knee flexion ( p < 0.001; η 2 > 0.35), all in favor of the EF group. This shows that EF during PEP improves hip and knee joint kinematics in the sagittal plane more than IF. Therefore, EF during PEP instructions is preferred to increase the effectiveness of this injury prevention program.